Accomplishment Motivation and Soft Skill Related to Learning Achievement - Junita, Diarni; Suarman, Suarman; Kartikowati, Sri (FKIP-Universitas Riau, 2018)
This study aims to determine the influence of achievementmotivation through the role of soft skills to the learning achievement. Thisresearch was conducted due to the low achievement motivation of students atEconomic Education Program Study, University of Riau. A total of 185samples were selected from 344 number of population using Yamanestatistical sampling technique. Data was collected by questionnaire anddocumentation techniques. It was then analyzed using path analysis. Theresults showed that Soft Skill played a positive role mediate that influence ofaccomplishment motivation on learning achievement. This means thatlearning achievement is not influenced by achievement motivation alone, butalso supported by soft skill as intervening variable. In order to achieveachievement motivation students should have a successful future orientedattitude. Meanwhile, to improve soft skill students must have the ability tocommunicate, adapt and build relationships obtained from the ability of ICTand foreign languages.